Measurement of Redox Biomarkers in the Whole Blood and Red Blood Cell Lysates of Dogs - Luis G. González-Arostegui; Alberto Muñoz-Prieto; Asta Tvarijonaviciute; José Joaquín Cerón; Camila Peres Rubio (MDPI AG, 2022)
The evaluation of the biomarkers of oxidative status is usually performed in serum, however, other samples, such as red blood cells (RBCs) lysates or whole blood (WB), can be used. The objective of this study was to evaluate if a comprehensive panel of redox biomarkers can be measured in the WB and RBCs of dogs, and their possible changes "in vitro" after the addition of different concentrations of ascorbic acid. The panel was integrated by biomarkers of the antioxidant status, such as cupric reducing antioxidant capacity (CUPRAC), ferric reducing ability of plasma (FRAP), Trolox equivalent antioxidant capacity (TEAC), thiol and paraoxonase type 1 (PON-1), and of the oxidant status, such as total oxidant status (TOS), peroxide-activity (POX-Act), reactive oxygen-derived compounds (d-ROMs), advanced oxidation protein products (AOPP) and thiobarbituric acid reactive substances (TBARS). All the assays were precise and accurate in WB and RBCs lysates. In addition, they showed changes after ascorbic acid addition that are in line with previously published results, being WB more sensitive to detect these changes in our experimental conditions. In conclusion, the panel of assays used in this study can be measured in the WB and RBCs of the dog. In particular, the higher sensitivity to detect changes in our experimental conditions and its easier sample preparation makes WB a promising sample for the evaluation of redox status in dogs, with also potential applications to other animal species and humans.